2018
DOI: 10.1097/01.aoa.0000532252.38893.c1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Death Due to Amniotic Fluid Embolism: A National Study in France

Abstract: (Anesth Analg. 2018;126(1):175–182) Signs and symptoms of amniotic fluid embolism (AFE) vary greatly and are not specific to AFE, making it a difficult condition to diagnose and treat. Recently, the Society for Maternal-Fetal Medicine (SMFM) and the AFE Foundation proposed 4 uniform diagnostic criteria to help identify cases of AFE for research purposes. These criteria have not been tested on a specific population. The authors of the present study applied these criteria to maternal deaths attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 0 publications
4
20
0
1
Order By: Relevance
“…Given these results, our study is in line with a French national study, including 36 cases of maternal mortality due to AFE, which showed that 41.7% of the cases did not satisfy at least 1 diagnostic criterion [8]. In their study, initial laboratory confirmation of DIC was also the most commonly unsatisfied criterion (28.9%), and the clinical onset time criterion of within 30 minutes after delivery was missed in 5.6% of women [8]. Moreover, according to a recent study by the Amniotic Fluid Embolism Case number of group I was 2, 7, 9, and 10 as shown in Table 2.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Given these results, our study is in line with a French national study, including 36 cases of maternal mortality due to AFE, which showed that 41.7% of the cases did not satisfy at least 1 diagnostic criterion [8]. In their study, initial laboratory confirmation of DIC was also the most commonly unsatisfied criterion (28.9%), and the clinical onset time criterion of within 30 minutes after delivery was missed in 5.6% of women [8]. Moreover, according to a recent study by the Amniotic Fluid Embolism Case number of group I was 2, 7, 9, and 10 as shown in Table 2.…”
Section: Discussionsupporting
confidence: 88%
“…Our results also showed that cases with at least 1 missing criterion manifested fatal maternal outcomes regarding maternal mortality and the amount of transfusion, similar to cases satisfying all 4 criteria. In this regard, we support the French national study that suggested extending the early documentation of DIC criteria of the SMFM to early clinical coagulopathy with bleeding [8].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations